2019
DOI: 10.15578/iaj.14.1.2019.31-38
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF SQUID LIVER MEAL IN MATURATION DIET ON GONADOSOMATIC INDEX AND GONADAL AMINO ACID CONTENT OF GOLDEN SPOTTED RABBITFISH, Siganus guttatus

Abstract: A four months feeding trial was conducted to evaluate the effects of two maturation diets containing either fishmeal (FM) or squid liver meal (SLM) as the major protein source on growth, gonadosomatic index and gonadal bio-chemical profiles of golden spotted rabbitfish, Siganus guttatus. The two tested diets were formulated to be iso-nitrogenous (40%) and iso-lipidic (14%) and supplemented with several micronutrients specifically for gonadal development. The initial weight of golden spotted rabbitfish used wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…The findings also demonstrated that application of floating diets containing CP content closely to requirement level for grow-out (33%) can also stimulate the gonadal development of rabbitifish up to the ealier stage of maturation. The GSI of oocyte obtained in this present study was lower (9%) compared when golden rabbitfish fed with maturation diet contained 40% CP [24]. This indicated that protein requirement for maturation stage of golden rabbitfish is higher than for grow-out.…”
Section: Hepatosomatic and Gonadosomatic Indexcontrasting
confidence: 44%
See 2 more Smart Citations
“…The findings also demonstrated that application of floating diets containing CP content closely to requirement level for grow-out (33%) can also stimulate the gonadal development of rabbitifish up to the ealier stage of maturation. The GSI of oocyte obtained in this present study was lower (9%) compared when golden rabbitfish fed with maturation diet contained 40% CP [24]. This indicated that protein requirement for maturation stage of golden rabbitfish is higher than for grow-out.…”
Section: Hepatosomatic and Gonadosomatic Indexcontrasting
confidence: 44%
“…The lower growth rate of fish fed floating feed containing 26% CP (FD1) obviously demonstrated that the protein level cannot support the proper growth rate of golden rabbitfish even at the bigger size. The mean final weight of 371.77±8.4 g in fish fed the FD2 diet may approach the size of maturation stage of golden rabbitfish [24].…”
Section: Growth Performance and Feed Utilizationmentioning
confidence: 97%
See 1 more Smart Citation